Biaxially oriented polyester film
Patent Information
- Application Number
- JP2020528140
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-11-22
- Filing Date
- 2018-11-09
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2038-11-09
AI Technical Summary
【0009】 本発明によれば、高耐熱性および高耐湿性に優れたポリエステル樹脂組成物およびこれを含むポリエステルフィルムが提供され得る。
Smart Images

Figure 0007644602000002 
Figure 0007644602000003 
Figure 0007644602000004
Abstract
Description
[Technical field]
[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims the benefit of priority to Korean Patent Application No. 10-2017-0156747, filed on November 22, 2017, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a polyester resin composition and a biaxially oriented polyester film containing the same. [Background technology]
[0003] Recently, metal materials are being replaced with plastic materials to reduce the weight of automobiles, but the plastic materials used in these automobile parts are required to have high heat resistance and be slim to reduce volume. Among the electrical equipment parts of these automobile parts, flexible flat cables (FFCs) are a type of connecting cable used to connect PCBs (Printed Circuit Boards) or PBAs (Printed Board Assembly), and are characterized by being relatively small and thin compared to general connectors. In addition, such FFCs are flexible and can be folded, and are widely used in connecting connectors in electronic devices such as mobile phones.
[0004] Usually, FFCs are manufactured using PET (Polyethylene terephthalate) stretched film, but since the heat resistance of PET stretched film is approximately 130℃, FFCs using PET stretched film cannot be applied to major parts such as automotive powertrains and engine control parts, which require high heat resistance. Therefore, attempts have been made to improve the heat resistance by using coating / laminating technology for PET stretched film, but the reality is that it is difficult to give PET stretched film high heat resistance to withstand high temperatures of 150℃ or more.
[0005] Polyimide films, which have high heat resistance, are also used for the above-mentioned FFC applications. However, since polyimide films are made of thermosetting resins, they have the disadvantage that they are difficult to reuse. Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention provides a polyester resin composition having excellent heat resistance and moisture resistance, and a biaxially oriented polyester film containing the same. [Means for solving the problem]
[0007] According to one embodiment of the present invention, there may be provided a polyester resin composition comprising a polycondensate of a dicarboxylic acid component including terephthalic acid and isophthalic acid and a diol component including cyclohexanedimethanol, the polyester resin having a melting temperature of 250°C or higher, a difference (Tm-Tmc) between the melting temperature (Tm) and the melt crystallization temperature (Tmc) of 45°C or higher, and a difference (Tcc-Tg) between the cold crystallization temperature (Tcc) and the glass transition temperature (Tg) of 40°C or higher.
[0008] According to another embodiment of the present invention, there may be provided a biaxially oriented polyester film formed using the polyester resin composition. Effect of the Invention
[0009] According to the present invention, it is possible to provide a polyester resin composition having excellent heat resistance and moisture resistance, and a polyester film containing the same. [Brief description of the drawings]
[0010] [Figure 1] 1 is a graph showing the results of measuring the moisture absorptivity of the films of Example 1 (PCT) and Comparative Example 1 (PET). [Diagram 2]1 is a graph showing the measurement results of hydrolysis resistance (intrinsic viscosity retention rate) of the films of Example 1 (PCT) and Comparative Example 1 (PET). [Diagram 3] 1 shows photographs of the film surfaces during evaluation of the hydrolysis resistance (intrinsic viscosity retention rate) of the films of Example 1 (PCT) and Comparative Example 1 (PET). [Figure 4] Photographs of the film surfaces of Example 1 (PCT) and Comparative Example 1 (PET) before and after oligomer evaluation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, a polyester resin composition and a biaxially oriented polyester film for flexible flat cables including the same according to specific embodiments of the present invention will be described in more detail.
[0012] The present inventors have experimentally confirmed that when a polyester resin containing a polycondensate of a dicarboxylic acid component containing terephthalic acid and isophthalic acid and a diol component containing cyclohexanedimethanol has a melting temperature of 250°C or more, a difference (Tm-Tmc) between the melting temperature (Tm) and the melt crystallization temperature (Tmc) of 45°C or more, and a difference (Tcc-Tg) between the cold crystallization temperature (Tcc) and the glass transition temperature (Tg) of 40°C or more, it is possible to produce an unstretched sheet having a thickness of 1.0 mm or more, and this can be used to increase the elongation when producing a stretched film, and to improve heat resistance and moisture absorption, thereby completing the invention.
[0013] Specifically, the biaxially stretched polyester film of the embodiment includes a polyester resin including a polycondensate of a dicarboxylic acid component including terephthalic acid and isophthalic acid and a diol component including cyclohexanedimethanol. The melting temperature of the polyester resin may be 250° C. or higher, 250 to 350° C., or 253 to 340° C. If the melting temperature of the polyester resin is less than 250° C., there is a problem that the heat resistance is low and the film cannot be applied to parts that require high heat resistance.
[0014] The polyester resin may have a difference (Tm-Tmc) between its melting temperature (Tm) and its melt crystallization temperature (Tmc) of 45° C. or more, 45 to 120° C., or 50 to 115° C. If the difference between the melting temperature and the melt crystallization temperature of the polyester resin is less than 45° C., the polyester resin is cooled from the molten state (near Tm) to the melt crystallized state (near Tmc) after the T-die, and is rapidly crystallized, resulting in a problem that it is difficult to form an unstretched sheet having a thickness of 1.0 mm or more and in a transparent state that can be stretched at the same time.
[0015] In addition, the polyester resin may have a difference (Tcc-Tg) between the cold crystallization temperature (Tcc) and the glass transition temperature (Tg) of 40° C. or more, 40 to 100° C., or 43 to 90° C. If the difference between the cold crystallization temperature and the glass transition temperature of the polyester resin is less than 40° C., when the polyester resin is heated to perform a process of stretching an unstretched sheet, the section from the glass transition state (Tg) to the cooling crystallization state (Tcc) becomes short, so that the polyester resin crystallizes rapidly, making it difficult to set the stretching processing conditions, and thus making it difficult to stretch the polyester resin.
[0016] That is, since the melting temperature of the polyester resin is 250°C or higher, it can exhibit high heat resistance, and since the difference between the melting temperature and the melt crystallization temperature is 45°C or higher, and the difference between the cold crystallization temperature and the glass transition temperature is 40°C or higher, it has excellent moldability and stretchability.
[0017] The content of isophthalic acid contained in the polyester resin may be 3-20 mol%, 5-20 mol%, 6-18 mol%, 8-16 mol%, or 10-14 mol% based on the total dicarboxylic acid component. If the content of isophthalic acid exceeds 20 mol%, the heat shrinkage rate is high at high temperatures of 150° C. or higher, and heat resistance is reduced. If the content is less than 3 mol%, the thickness of the transparent unstretched sheet is very limited to about 0.1 mm, and the stretching ratio is also limited, so that the elongation rate is reduced during the production of a stretched film, and desired mechanical properties and heat resistance cannot be obtained.
[0018] The molar ratio of the dicarboxylic acid component and the diol component contained in the polyester resin may be 1:1 to 2, or 1:1.2 to 1.8. If the molar ratio of the dicarboxylic acid component and the diol component is less than 1:1, the melting temperature is lowered and the heat resistance is reduced, whereas if the molar ratio exceeds 1:2, the moldability is rather reduced and desired mechanical properties cannot be obtained.
[0019] The dicarboxylic acid component may further include, in addition to the terephthalic acid and isophthalic acid, one or more other dicarboxylic acid components selected from the group consisting of 2,6-naphthalenedicarboxylic acid, dimethylisophthalic acid, and dimethyl 2,6-naphthalenedicarboxylic acid, but is not limited thereto. The content of the other dicarboxylic acid components may be 20 mol% or less, 0.1 to 20 mol%, or 5 to 15 mol% based on the total dicarboxylic acid components.
[0020] The diol component may further include an aliphatic diol having 2 to 20 carbon atoms, for example, one or more other diol components selected from the group consisting of ethylene glycol, diethylene glycol, 1,4-butanediol, 1,3-propanediol, and neopentyl glycol, but is not limited thereto. The content of the other diol components may be 20 mol% or less, 0.1 to 20 mol%, or 5 to 15 mol% based on the total diol components.
[0021] The polyester resin may have an intrinsic viscosity (IV) of 0.4 to 1.2 dl / g, 0.5 to 1.0 dl / g, or 0.7 to 0.9 dl / g. If the intrinsic viscosity is less than 0.4 dl / g, the melting temperature is lowered and the heat resistance is reduced, whereas if it exceeds 1.2 dl / g, the moldability is reduced and desired mechanical properties cannot be obtained.
[0022] The polyester resin may have a number average molecular weight of 15,000 to 50,000 g / mol, 20,000 to 45,000 g / mol, or 25,000 to 40,000 g / mol. If the number average molecular weight is less than 15,000 g / mol, the melting temperature is lowered and heat resistance is reduced, whereas if it exceeds 50,000 g / mol, moldability is reduced and desired mechanical properties cannot be obtained.
[0023] The polyester resin may have a weight average molecular weight of 50,000 to 150,000 g / mol, 60,000 to 140,000 g / mol, or 70,000 to 130,000 g / mol. If the weight average molecular weight is less than 50,000 g / mol, the melting temperature is lowered and the heat resistance is reduced, whereas if it exceeds 150,000 g / mol, the moldability is reduced and desired mechanical properties cannot be obtained.
[0024] The polyester resin preferably has a melt crystallization temperature of 150 to 230° C. If the polyester resin has a melt crystallization temperature of less than 150° C., the heat setting effect decreases during post-processing or actual use of the stretched film, making it difficult to impart dimensional stability to the final stretched film, specifically, high shrinkage may occur. If the melt crystallization temperature exceeds 230° C., it is difficult to produce a transparent unstretched sheet during film extrusion.
[0025] According to another embodiment of the present invention, there is provided a biaxially oriented polyester film formed using the polyester resin composition. The biaxially oriented polyester film exhibits heat resistance at high temperatures of 150 to 200°C, and can therefore be generally applied to safety parts such as automotive powertrains, engine controls, and steering devices, and can be particularly used as a material for flexible flat cables (FFCs) that require excellent heat resistance, moisture resistance, electrical insulation properties, etc.
[0026] Typically, PET film is used as a flexible flat cable material, which can control the thickness up to 1.2 mm when unstretched, but PET film has the disadvantage of being vulnerable to heat, with a heat resistance of approximately 130°C.Therefore, there have been attempts to use polycyclohexylene dimethylene terephthalate (PCT) film for parts that require heat resistance, but conventional PCT films have high glass transition temperature (Tg) and melting temperature (Tm).
[0027] However, conventional PCT films have a high melt crystallization temperature (Tmc), and crystallization occurs rapidly immediately after extrusion using a T-die, etc., which causes a problem that the thickness of the transparent unstretched sheet is very limited to about 0.1 mm. When the thickness of the transparent unstretched sheet is as thin as about 0.1 mm, the elongation rate is low during the stretching process. Meanwhile, conventional PCT films have a low cold crystallization temperature (Tcc), and when the temperature is raised (heated) to perform the stretching process of the unstretched sheet, the section from the glass transition state (Tg) to the cooling crystallization state (Tcc) is short, causing rapid crystallization, making it difficult to set the stretching processing conditions, and thus making stretching difficult.
[0028] However, the polyester resin according to the embodiment has a difference (Tm-Tmc) between the melting temperature (Tm) and the melt crystallization temperature (Tmc) of 45° C. or more, and the polyester resin has a difference (Tcc-Tg) between the cold crystallization temperature (Tcc) and the glass transition temperature (Tg) of 40° C. or more, so that the crystallization rate can be delayed immediately after extrusion, and the maximum thickness of the transparent unstretched sheet can be controlled to about 1.2 mm, which is similar to the thickness of the transparent unstretched sheet of a PET film. In addition, since the crystallization rate can be delayed in the stretching process, the unstretched sheet can be easily stretched, and the heat resistance of the polyester film can be improved.
[0029] The biaxially oriented polyester film according to another embodiment may be a multi-layer film having two or more layers in which the polyester resin composition is co-extruded, or a laminate (thermal bonding) film.
[0030] Specifically, two or more of the polyester resin compositions are melted in different extruders, and the molten resins are fed into a die to laminate two or more layers, and then a non-stretched multilayer film (or laminate film) can be provided by a method such as blowing or casting. Each layer included in the non-stretched multilayer film can be transparent and have a thickness of about 1.2 mm or more. In this case, the two or more polyester resin compositions can be the same composition or compositions with different components or contents. In addition, the non-stretched multilayer film can be biaxially stretched in the longitudinal and transverse directions to obtain a biaxially stretched polyester film with excellent heat resistance.
[0031] The biaxially stretched polyester film may have a heat shrinkage rate of less than 0.5%, 0.01 to 0.4%, or 0.01 to 0.3% for 30 minutes at 150° C., and may have a heat shrinkage rate of less than 1.0%, 0.01 to 0.9%, or 0.01 to 0.8% for 30 minutes at 200° C. Such a biaxially stretched polyester film has a significantly low heat shrinkage rate at temperatures of 150 to 200° C., and therefore, it can be confirmed that the biaxially stretched polyester film has excellent heat resistance.
[0032] The biaxially oriented polyester film has excellent moisture resistance, specifically, when the temperature is 85° C. and the relative humidity is 85%, the moisture absorption resistance can be 1% or less, 0.01 to 0.9%, or 0.01 to 0.8%.
[0033] On the other hand, the method for producing the biaxially stretched polyester film is not limited thereto, but for example, the polyester resin composition is vacuum dried to thoroughly remove moisture, and then fed to an extruder, melt extruded at a temperature of 200 to 300°C, and molded into a sheet shape from a T-shaped die. The sheet-shaped product thus obtained is cooled and solidified on a mirror-finished cooling drum to obtain an unstretched sheet. At this time, it is preferable to use an electrostatic application method in order to increase adhesion with the cast drum. Thereafter, the obtained unstretched sheet is stretched in the longitudinal direction (length direction or machine direction, MD; mechanical direction). It is desirable that the longitudinal stretching lowers the crystal orientation and also promotes thermal crystallization. After the longitudinal stretching, the film is stretched in the transverse direction (width direction, TD; trans machine direction) and heat-treated to obtain a biaxially stretched film.
[0034] In this case, the stretching ratio may be 2 to 5 times, preferably 2.5 to 5 times, more preferably 2.5 to 4.0 times in the machine direction, and 2.5 to 5 times, preferably 3 to 4.5 times, more preferably 3.2 to 4.2 times in the transverse direction.
[0035] The stretching temperature may be in the range of glass transition temperature (Tg) of the polyester resin +5°C to Tg +50°C, or in the range of Tg +10°C to Tg +40°C. At this time, the lower the Tg, the better the stretchability, but breakage may occur. When the stretching temperature is particularly in the range of Tg +10°C to Tg +40°C, the brittleness of the produced film can be improved.
[0036] The longitudinal stretching speed may be 22 to 500 m / min, 25 to 400 m / min, or 25 to 200 m / min. In this case, when the longitudinal stretching speed is 22 m / min or more, it is advantageous to maintain the orientation aimed at in the present invention, and since the crystallinity is imparted by the longitudinal stretching speed and the stretch ratio, the transverse stretching speed varies depending on the longitudinal stretching conditions. EXAMPLES
[0037] The present invention will be described in more detail with reference to the following examples, however, the following examples are merely illustrative of the present invention and are not intended to limit the scope of the present invention.
[0038] Example 1 1) Production of polyester resin composition 2.0 kg of 1,4-cyclohexanedimethanol, 1.8 kg of dicarboxylic acid containing terephthalic acid and isophthalic acid in a molar ratio of 95 mol%:5 mol%, 0.4 g of triethyl phosphate, 0.2 g of titanium oxide catalyst (Hombifast PC, manufactured by Sachtleben, Ti atom content in catalyst: 15 wt%), and 0.2 g of antimony trioxide (antimony atom content in catalyst: 83.5 wt%) were added to a reactor, and the temperature was raised to 280°C at normal pressure for 3 hours to carry out an esterification reaction. Next, the esterification reaction product was polycondensed by heating it at a temperature of 295°C under a pressure of 0.5 to 1 torr for 150 minutes to produce a polyester resin, which was then processed into chips.
[0039] 2) Manufacturing of biaxially oriented polyester film The polyester resin chips were melt-extruded in an extruder, formed into a sheet, and cooled. The sheet obtained was stretched 3.6 times in the machine direction (MD) and then 3.8 times in the transverse direction (TD). The stretched film was heat-set at 238°C to obtain a biaxially stretched polyester film.
[0040] Examples 2 and 3 A biaxially stretched polyester film was obtained in the same manner as in Example 1, except that the isophthalic acid was used in the molar ratio shown in Table 1 below.
[0041] Comparative Example 1 1.2 kg of terephthalic acid and 1.2 kg of ethylene glycol were put into a reactor and a normal polymerization reaction was carried out at 258°C to produce a polyethylene terephthalate (PET) polymer, which was then processed in the form of chips. This was melt-extruded in an extruder, formed into a sheet, cooled, stretched 3.7 times in the machine direction (MD), and then stretched 4.0 times in the transverse direction (TD) to produce a polyethylene terephthalate film.
[0042] Comparative Examples 2 to 5 A biaxially stretched polyester film was obtained in the same manner as in Example 1, except that the isophthalic acid was used in the molar ratio shown in Table 1 below.
[0043] evaluation 1. Measurement of glass transition temperature etc. by DSC analysis The polyester resins of Examples 1 to 3 and Comparative Examples 1 to 5 were analyzed by DSC (Differential Scanning Calorimeter) to measure the glass transition temperature (Tg), cold crystallization temperature (Tcc), melting temperature (Tm), and melt crystallization temperature (Tmc). Specifically, the polyester resin was heated from 30°C to 320°C at a heating rate of 10°C / min using DSC, maintained for 5 minutes, quenched to 30°C, and maintained for 5 minutes. Thereafter, the glass transition temperature (Tg), cold crystallization temperature (Tcc), and melting temperature (Tm) were measured while heating from 30°C to 320°C at a heating rate of 10°C / min. After maintaining at 320°C for 5 minutes, the melt crystallization temperature (Tmc) was measured while cooling to 30°C at a cooling rate of 10°C / min, and the results are shown in Table 1 below.
[0044] 2. Maximum thickness measurement of transparent unstretched sheet The polyester resins of Examples 1 to 3 and Comparative Examples 1 to 5 were melt extruded in an extruder, and before being stretched in the machine direction (MD) and transverse direction (TD), the maximum thickness of the unstretched sheet in a transparent state was measured. The results are shown in Table 1 below.
[0045] 3. Measurement of maximum elongation The unstretched sheets of Examples 1 to 3 and Comparative Examples 1 to 5 were biaxially stretched in both the machine direction and the cross direction, and the maximum elongation was measured. The results are shown in Table 1 below.
[0046] 4.Measurement of area thermal shrinkage rate For the films of Examples 1 to 3 and Comparative Examples 1 to 5, one end was cut parallel to the machine direction (longitudinal direction) and the other end was cut perpendicular to the machine direction (transverse direction) to prepare a square film sample of 10 cm x 10 cm. After the film was kept in an air-circulating oven at 150°C for 30 minutes, the sample was taken out and the change in length in each of the longitudinal and transverse directions was measured at room temperature, and the thermal shrinkage in the longitudinal and transverse directions was calculated by the following formula 1. In the same manner, the film was kept in an oven at 200°C for 30 minutes, and the thermal shrinkage was calculated, and the results are shown in Table 1 below. [Formula 1] Heat shrinkage rate (%) = [(L0-L) / L0] x 100 In the above formula, L0 is the length before heat treatment, and L is the length after heat treatment.
[0047] 5. Evaluation of Tensile Elongation Retention Rate The films of Example 1 (PCT) and Comparative Example 1 (PET) were maintained at a temperature of 121°C, a relative humidity of 100% and an atmospheric pressure of 2 atm (Pressure Cooker Test, high temperature and high humidity test) for 48 hours and 60 hours, and then the tensile elongation retention was measured. The results are shown in Table 1 below.
[0048] 6. Moisture absorption resistance evaluation The films of Example 1 (PCT) and Comparative Example 1 (PET) were maintained at a temperature of 85° C. and a relative humidity of 85% for 5,000 hours, and the weight gain was measured and shown in the graph in Figure 1. In addition, the moisture absorption rate after 5,000 hours was calculated, and the results are shown in Table 1 below.
[0049] 7.Evaluation of hydrolysis resistance (1) Intrinsic viscosity measurement The films of Example 1 and Comparative Example 1 were dissolved in o-chlorophenol to a concentration of 1.2 g / dl, and the intrinsic viscosity was measured at 35° C. using an Ubbelodhe viscometer.
[0050] (2) Measurement of hydrolysis resistance (intrinsic viscosity retention rate) The films of Example 1 and Comparative Example 1 were maintained at a temperature of 85° C. and a relative humidity of 85%, and the extent to which the intrinsic viscosity was maintained was then measured, and the results are shown in the graph of Figure 2. The hydrolysis resistance (intrinsic viscosity maintenance rate) after 5,000 hours is also shown in Table 1 below. The surfaces of Example 1 (PCT) and Comparative Example 1 (PET) after 5,000 hours were photographed and are shown in Figure 3.
[0051] 8. Oligomer Evaluation In order to check for oligomer elution from the films of Example 1 and Comparative Example 1, the films were heat-treated in an oven at 150° C. for about 60 minutes, and then the changes were observed and measured using a haze meter. The results are shown in Table 1 below.
[0052] Haze Meter: NIPPON DENSHOKU, model NDH-7000 9. Dielectric breakdown voltage evaluation Flexible flat cables were manufactured using the films of Example 1 and Comparative Example 1, and a voltage of 1,000 V AC was applied to the adjacent conductors for 60 seconds. The voltage at which the film broke down and short-circuited was read, and the results are shown in Table 1 below.
[0053] [Table 1]
[0054] -IPA * : Content of isophthalic acid (IPA) relative to 100 mol% of dicarboxylic acid components contained in polyester resin -PCT ** : Pressure Cooker Test (PCT) or Autoclave Test, a test to evaluate whether a product can withstand high temperature / high humidity environments. The test is conducted under conditions of 121°C temperature, 100% relative humidity, and 2atm air pressure.
[0055] According to Table 1 above, it was confirmed that the PCT films of Examples 1 to 3 have lower heat shrinkage rates and better heat resistance, as well as better moisture absorption resistance, hydrolysis resistance, and electrical properties than the PET film of Comparative Example 1.
[0056] It was also confirmed that the PCT films of Examples 1 to 3 had higher maximum elongation, lower thermal shrinkage, and better heat resistance than the PCT films of Comparative Examples 2 to 5. It was also confirmed that the PCT films of Examples 1 to 3 could control the thickness of the unstretched sheet to be thicker than the PCT films of Comparative Examples 2 and 3.
Claims
1. The polyester resin includes a polycondensate of a dicarboxylic acid component including terephthalic acid and isophthalic acid and a diol component including cyclohexanedimethanol, The content of the isophthalic acid is 3 to 20 mol % based on the total dicarboxylic acid components, and the content of the terephthalic acid is 80 to 97 mol % based on the total dicarboxylic acid components. The content of the cyclohexanedimethanol is 80 to 100 mol % based on the total diol components, The diol component includes one or more other diol components selected from the group consisting of ethylene glycol, diethylene glycol, 1,4-butanediol, 1,3-propanediol, and neopentyl glycol, in an amount of 0 to 20 mol % based on the total diol components; The polyester resin has a number average molecular weight of 15,000 to 50,000 g / mol; The polyester resin has an intrinsic viscosity (IV) of 0.4 to 0.9 dl / g; The polyester resin has a melting temperature of 250° C. or higher and 350° C. or lower, The polyester resin has a difference (Tm-Tmc) between its melting temperature (Tm) and its melt crystallization temperature (Tmc) of 45°C or more and 120°C or less, The polyester resin has a difference (Tcc-Tg) between its cold crystallization temperature (Tcc) and its glass transition temperature (Tg) of 40° C. or more and 100° C. or less, The melting temperature (Tm), the cold crystallization temperature (Tcc) and the glass transition temperature (Tg) are measured by using a Differential Scanning Calorimeter (DSC) while heating the polyester resin from 30° C. to 320° C. at a heating rate of 10° C. / min, maintaining the temperature for 5 minutes, rapidly cooling to 30° C., maintaining the temperature for 5 minutes, and then heating from 30° C. to 320° C. at a heating rate of 10° C. / min. The melt crystallization temperature (Tmc) is measured by maintaining the temperature at 320° C. for 5 minutes after the heating, and then cooling to 30° C. at a cooling rate of 10° C. / min. It is formed using a polyester resin composition, The polyester resin composition is a coextruded multilayer film or laminate film having two or more layers. Biaxially oriented polyester film.
2. The dicarboxylic acid component includes one or more other dicarboxylic acid components selected from the group consisting of 2,6-naphthalenedicarboxylic acid, dimethylisophthalic acid, and dimethyl 2,6-naphthalenedicarboxylic acid, in an amount of 0 to 17 mol % based on the total dicarboxylic acid components; 2. The biaxially oriented polyester film according to claim 1.
3. The molar ratio of the dicarboxylic acid component and the diol component is 1:1 to 2.
2. The biaxially oriented polyester film according to claim 1.
4. The polyester resin has a weight average molecular weight of 50,000 to 150,000 g / mol.
2. The biaxially oriented polyester film according to claim 1.
5. The polyester resin has a melt crystallization temperature of 150 to 230° C.
2. The biaxially oriented polyester film according to claim 1.
6. The biaxially oriented polyester film is for flexible flat cables or PCBs (Printed Circuit Boards).
2. The biaxially oriented polyester film according to claim 1.
7. The biaxially oriented polyester film has a heat shrinkage rate of less than 0.5% for 30 minutes at 150°C and a heat shrinkage rate of less than 1.0% for 30 minutes at 200°C.
2. The biaxially oriented polyester film according to claim 1.
8. The biaxially oriented polyester film is stretched 2 to 5 times in the machine direction (MD) and 2 to 5 times in the transverse direction (TD).
2. The biaxially oriented polyester film according to claim 1.
9. The biaxially oriented polyester film has a tensile elongation retention rate of 50% to 75% after 48 hours and a tensile elongation retention rate of 30% to 60% after 60 hours in a high temperature and high humidity test (Pressure Cooker Test) under conditions of a temperature of 121° C., a relative humidity of 100%, and an atmospheric pressure of 2 atm.
2. The biaxially oriented polyester film according to claim 1.
10. The biaxially oriented polyester film has a moisture absorption resistance of 1% or less when the temperature is 85° C. and the relative humidity is 85%.
2. The biaxially oriented polyester film according to claim 1.
Citation Information
Patent Citations
Polyester film
JP1990170824A
Flexible magnetic recording disk
JP1991241518A
Heat-resistant copolyester film and container
JP1994500809A
Multicomponent polyester / polycarbonate blend with improved impact strength and processability
JP1995509009A
Film for flexible printed circuit board
JP2005129699A